Randomized Clinical Trial with e-MotionalTraining® 1.0 for Social Cognition Rehabilitation in Schizophrenia - Maroño Souto, Yolanda; Vázquez Campo, Miriam; Díaz Llenderrozas, Francisco; Rodríguez Álvarez, Marina; Mateos, Raimundo; García Caballero, Alejandro (Frontiers in Psychiatry, 2018)
Background Schizophrenia patients present deficits in social cognition (SC), emotion and social perception, theory of mind (ToM) and attributive style (AS). This study tested the efficacy, in real clinical conditions, of a online self- training program in social cognition, e-Motional Training®, in comparison with treatment as usual (TAU). Method: A randomized single blinded multicenter clinical trial was conducted with 60 schizophrenia stable outpatients. All patients (control and intervention) were treated with drug therapy, case management and individual and group psychotherapy (not focused on social cognition). Intervention group was treated with e-Motional Training®, an online program devised for SC rehabilitation. Statistical analysis: A descriptive analysis and parametric/ non-parametric tests were used to compare both groups at baseline. Analysis of covariance (ANCOVA) was used to compared post–pre changes in SC between the two interventions. If the group effect was significant, follow-up univariate test (t-test for dependent samples) was carried out in each group to verify whether the effect was due to improvement in the intervention group or deterioration in the control group. We considered statistically significant differences with P < 0.05. Results: Significant improvements were obtained in the intervention group in Emotion recognition (ER) and most ToM variables in comparison with the control group. Discussion: e-Motional Training® seems to be a promising online training tool for social cognition deficits in schizophrenia, covering the lack of similar intervention instruments in our community.